The relation between informal caregiver’s stress towards quality of life stroke patients - Imarta Retri Putri; Arman Yurisaldi Saleh; Mila Citrawati (Konselor, 2020)
One of the main problem in stroke patients is how the family provided the needs and also the assistance to improve their abilities even within limitations, so that the quality of life becomes meaningful. The stress on caregivers is an important factor to consider the ability of caregivers to provide care. This study aimed to determine the relation of informal caregiver stress levels to the quality of life of stroke patients in RSUD Kota Depok period 2019. The method used analytical study with a cross sectional design, sample of this study was 36 outpatients at the Neurology Polyclinic taken by purposive sampling technique. This study was analyzed by gamma and somers’d test and the results showed that there was a relation between the informal caregiver’s stress level (p = 0.001; r: -0.475) with quality of life stroke patients. This study concluded that informal caregiver stress levels related to the quality of life of stroke patients.